ANALISIS KELAYAKAN USAHA CABAI KERITING ORGANIK DI DESA JAYAPURA KECAMATAN JAYAPURA KABUPATEN OKU TIMUR - Pudiyaka (Jurnal Bakti Agribisnis, 2015)
The purpose of this research is to: (1) To know whether from the profit of chili pepper management business can fulfill the needs of his family in Jayapura Village, Jayapura Subdistrict, OKU Timur Regency, (2) To know whether the profit contributed to households in Jayapura Village Kecamatan Jayapura, Kabupaten OKU Timur, (3) To know the feasibility level of chili plant management business in Jayapura Village, Jayapura District, East OKU Regency. This research has been conducted in Jayapura Village, Jayapura District, East OKU Regency, there is a business actor of chilli plant, with survey method. This research was conducted from December 2012 until February 2013. This research found that Chili business gives Benefit for chilli business actor in Jayapura Village Jayapura District with the amount of cost sacrificed in one production process is smaller than acceptance of chili cultivation in Jayapura Village, Jayapura District That is, the amount of cost that is sacrificed on average is Rp 16.022.305, - / Lg. With an average revenue of Rp. 32.283.240, - / Lg. And the average amount of revenue earned amounted to Rp 16,260,935, - / Lg. The income from chili farming in Jayapura Village, Jayapura Sub-district, contributed to the income of the family, on average, the main income is from the cultivation business of chili Rp 16.260.935, - / Lg. And other income from rice farming of business actors of Chili as much as Rp. 2,233,187, - with a contribution value of 73.53%.